Using biometric techniques to secure online student assessment: Comparative study - Ibrahim, Jamaludin; Ali, Muna A.; Nassr, Rasheed (LJS Publisher and IJCSIS Press, 2011)
Currently E-learning systems do not provide a tool to authenticate student continuously during online assessment, this raises the probability of cheating. Many proposed solutions use different biometric techniques to identify and authenticate student continuously, they use different techniques with different measures. This paper proposes certain criteria that should be available in any proposed biometric technique to be fitted with e-learning architecture and continues authentication of student during online assessment. This paper investigates some proposed solutions to see compatibility of those solutions with the proposed criteria